2010
DOI: 10.1159/000320324
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Interrelations in Lifespan Development and Aging: How Does 1 + 1 Make a Couple? – Introduction

Abstract: Lifespan development and aging do not take place in a vacuum. It is increasingly recognized that others, who may be very familiar such as marital partners, often play a key role in shaping the developmental trajectories of their spouses. Further, this shaping seems at least partially dependent on the prolonged interactions that result in a high level of familiarity that is conducive to affecting the feelings, actions and reactions of the other member of the dyad. The studies comprising this special series on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…By the same token, a smaller social network may also mean members have a more meaningful impact on aging adults' well being. As such, it is important to explore the impact of close partners on aging adults' QoL Marriage plays a central role in affecting the course of success ful aging (Hoppmann, Gerstorf, & Luszcz, 2011). Interdependence theory posits that married people's patterns of behavior-whether positive or negative-can affect their partners because of noninde pendent nature of their relationship (Cook & Kenny, 2005;Kelley & Thibault, 1978).…”
Section: Interpersonal Effects Of Health Cognition and Qolmentioning
confidence: 99%
“…By the same token, a smaller social network may also mean members have a more meaningful impact on aging adults' well being. As such, it is important to explore the impact of close partners on aging adults' QoL Marriage plays a central role in affecting the course of success ful aging (Hoppmann, Gerstorf, & Luszcz, 2011). Interdependence theory posits that married people's patterns of behavior-whether positive or negative-can affect their partners because of noninde pendent nature of their relationship (Cook & Kenny, 2005;Kelley & Thibault, 1978).…”
Section: Interpersonal Effects Of Health Cognition and Qolmentioning
confidence: 99%
“…Kiecolt-Glaser & Newton, 2001;Walker & Luszcz, 2009). Dyadic studies have demonstrated the interdependence and the influence of mutual spousal interrelations in domains such as cognitive functioning, health and wellbeing (Hoppmann, Gerstorf, & Luszcz, 2011;Walker & Luszcz), by analyzing data from both spouses within the unit of the couple. Since late-life spouses engage in frequent interaction in their everyday life (Antonucci, Akiyama, & Takahashi, 2004;Lang, 2001), it is to be expected that they will influence each other in their everyday activities.…”
Section: Introductionmentioning
confidence: 99%
“…Individual development does not take place in isolation but is invariably embedded within a social context such as a spousal relationship . Marital partners play a key role in shaping individuals' developmental trajectories, and this is particularly true for older couples who have a long history of joint experiences (Hoppmann, Gerstorf, & Luszcz, 2011). Because of the shared family environment and mutual influence, a husband and wife often show interrelations in domains of emotional experience, cognitive functioning, attitude, and well-being (Desai, Schimmack, Jidkova, & Bracke, 2012;Druley, Stephens, Martire, Ennis, & Wojno, 2003;Gerstorf, Hoppmann, Anstey, & Luszcz, 2009).…”
Section: Dyadic Perspective On Tgp Fga and Life Satisfactionmentioning
confidence: 99%